2016
DOI: 10.1016/j.brs.2016.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Subject Consistency and Reliability of Response Following 2 mA Transcranial Direct Current Stimulation

Abstract: . (2016) Intrasubject consistency and reliability of response following 2mA transcranial direct current stimulation. Brain Stimulation, 9 (6). pp. 819-825. ISSN 1876-4754 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/34423/1/Dyke%20et%20al%2018-6-16.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Creative C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 27 publications
(37 reference statements)
3
44
1
Order By: Relevance
“…To better compare our findings with previous studies, we also calculated the ICCs for Grand Mean post-tDCS amplitudes (the mean of all post-tDCS measures, as done in [27, 29, 33, 34]. This analysis showed poor to fair reliability of tDCS post-effects (ICC range = 0.076 – 0.545; Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…To better compare our findings with previous studies, we also calculated the ICCs for Grand Mean post-tDCS amplitudes (the mean of all post-tDCS measures, as done in [27, 29, 33, 34]. This analysis showed poor to fair reliability of tDCS post-effects (ICC range = 0.076 – 0.545; Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Accordingly, Dyke and colleagues (2016) showed that 2mA-atDCS increased M1 excitability consistently across four sessions (electrode size: 35cm 2 ; current density: 0.058 mA/cm 2 ; tDCS duration: 20min), whereas no change was induced by cathodal or sham stimulation [34]. Another recent study also performed three different tDCS conditions (anodal, cathodal, sham) repeating each condition three times (electrode size: 35cm 2 ; current density: 0.029 mA/cm 2 ; tDCS duration: 10min).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that even the influence of stimulation on motor-evoked potentials-the primary proof of tDCS efficacy in humans-is subject to high inter- (López-Alonso et al 2014;Strube et al 2016;Wiethoff et al 2014) and intraindividual variability (Dyke et al 2016;Horvath et al 2015b;López-Alonso et al 2015). The ultimate solution may be to tailor stimulation dosage and placement of electrodes to individual brains, but this requires sophisticated computational modeling efforts that are only just getting under way (Berker et al 2013;Bikson et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that AtDCS aftereffects can show variability between-subjects717273, where some individuals do not show potentiation of MEPs after AtDCS application. We therefore screened out non-responders to AtDCS based on post-AtDCS MEP changes in the baseline session.…”
Section: Methodsmentioning
confidence: 99%
“…Six individuals did not meet this criterion and were therefore excluded from the study. Importantly, the intra-subject consistency of AtDCS responses across multiple sessions is poorly understood, but might be a factor that can influence the group occlusion magnitude717274.…”
Section: Methodsmentioning
confidence: 99%